Elucidating the biodegradation pathway and catabolic genes of benzophenone-3 in Rhodococcus sp. S2-17. (15th April 2022) - Baek, Ju Hye; Kim, Kyung Hyun; Lee, Yunhee; Jeong, Sang Eun; Jin, Hyun Mi; Jia, Baolei; Jeon, Che Ok
Abstract: A new bacterium, Rhodococcus sp. S2-17, which could completely degrade an emerging organic pollutant, benzophenone-3 (BP-3), was isolated from contaminated sediment through an enrichment procedure, and its BP-3 catabolic pathway and genes were identified through metabolic intermediate and transcriptomic analyses and biochemical and genetic studies. Metabolic intermediate analysis suggested that strain S2-17 may degrade BP-3 using a catabolic pathway progressing via the intermediates BP-1, 2, 4, 5-trihydroxy-benzophenone, 3-hydroxy-4-benzoyl-2, 4-hexadienedioic acid, 4-benzoyl-3-oxoadipic acid, 3-oxoadipic acid, and benzoic acid. A putative BP-3 catabolic gene cluster including cytochrome P450, flavin-dependent oxidoreductase, hydroxyquinol 1, 2-dioxygenase, maleylacetate reductase, and α/β hydrolase genes was identified through genomic and transcriptomic analyses. Genes encoding the cytochrome P450 complex that demethylates BP-3 to BP-1 were functionally verified through protein expression, and the functions of the other genes were also verified through knockout mutant construction and intermediate analysis. This study suggested that strain S2-17 might have acquired the ability to catabolize BP-3 by recruiting the cytochrome P450 complex and α/β hydrolase, which hydrolyzes 4-benzoyl-3-oxoadipic acid to benzoic acid and 3-oxoadipic acid, genes, providing insights into the recruitment of genes of for the catabolism of emerging organic pollutants. Graphical abstract: Image 1 Highlights: Rhodococcus sp. S2-17 capable of completely biodegrading benzophenone-3 was isolated. Catabolic pathway of BP-3 in strain S2-17 was proposed through metabolite analysis. BP-3 catabolic genes were elucidated through genome, transcriptomic, and biochemical analyses. Catabolic genes of BP-3 in strain S2-17 may have been acquired via lateral gene transfer.